Protein Tyrosine Kinase Gene Expression Profiles in the Embryonic Bursa of Fabricius of Chicken Lines Selected for High and Low Antibody Responses - Nuthalapati, Nikhil; Burks, Tyler A.; Siegel, Paul B.; Taylor, Jr, Robert L.; Pharr , Gregory T. (International Journal of Poultry Science, 2021)
Background and Objective: The chicken lines selected for high (HAS line) and low (LAS) antibody responses to antigenic challenge represent a valuable model for identifying genes controlling the development of humoral immunity. In this study, we evaluated the expression of receptor tyrosine kinase (RTK) and non-receptor tyrosine kinase (nRTK) genes in the developing bursa from both chicken lines. These genes have a critical role in cell survival, migration and differentiation. In addition, we examined bursas from embryos exposed to testosterone, to detect changes in the expression of these genes when normal bursa development was inhibited. Materials and Methods: cDNA was synthesized from whole bursa RNA and PCR amplified with degenerate primers. The nucleotide sequence of the PCR products was analyzed with the NCBI database. Results: A total of 172 cDNAs from the HAS and 183 cDNAs from the LAS lines were sequenced. The most abundant nRTK and RTK cDNAs were from the Fyn-related kinase (FRK) and Ephrin A1 receptor (EphA1) genes and the expression levels differed significantly between the HAS and LAS bursas. Embryonic exposure to testosterone increased the number of cDNAs from the FRK gene. Conclusion: The significant differences in transcription of the FRK and EphA1 genes due to genetic selection may result in differences in bursal development between the HAS and LAS lines. Testosterone treatment significantly modulated FRK expression, which suggests a role for this gene in the differentiation and organization of the epithelium in the developing bursa.